2015
DOI: 10.1063/1.4914847
|View full text |Cite
|
Sign up to set email alerts
|

Raising efficiency of organic solar cells with electrotropic additives

Abstract: Incorporation of electrotropic additives with large molecular dipole moments into the bulk heterojunction layer of organic photovoltaic devices followed by electric field poling led to an increase of power conversion efficiency up to 7.97% from 7.17% for devices that did not utilize the additives and from 5.18% for devices with additives prior to poling. The improvement is due to more efficient extraction of photogenerated charge carriers, resulting in higher short circuit current density and fill factor. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Therefore, energy generation focus has been shifted more towards alternative renewable energy sources. During the last 12 years, enormous work is being pursued on silicon solar cell, perovskite solar cell, organic solar cell, thermoelectric materials and production of hydrogen for fuel cell [2][3][4][5][6][7][8][9]. The share of renewable energy in a global electricity generation approached 22.8% in 2014, making them the third largest contributor just behind coal and gas [10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, energy generation focus has been shifted more towards alternative renewable energy sources. During the last 12 years, enormous work is being pursued on silicon solar cell, perovskite solar cell, organic solar cell, thermoelectric materials and production of hydrogen for fuel cell [2][3][4][5][6][7][8][9]. The share of renewable energy in a global electricity generation approached 22.8% in 2014, making them the third largest contributor just behind coal and gas [10].…”
Section: Introductionmentioning
confidence: 99%
“…This is also seen in the individual EPR spectra of C 60 -N and C 70 -N ( Figure S7A,C ) and is consistent with a molecular dipole oriented from the fullerene cage to the tertiary amines. 48 , 49 Interestingly, the EPR signal intensified when irradiated with white light (70 mW cm –2 ), indicative of photoenhanced self-doping ( Figure 3 C, Figure S7A,C ). Current – voltage ( I – V ) measurements confirmed that photocurrent within the C 60 /C 70 -N thin films is nearly 1 order of magnitude larger than in the dark ( Figure 3 D).…”
Section: Resultsmentioning
confidence: 99%
“…An effective approach to suppress the diffusion loss in OSCs is to increase the built-in electric field across the active layer. 18 This can be realized by using a high-work function material as the anode and a low-work function material as the cathode. 19 For this purpose, doped materials, such as ZnO, 20,21 MoO 3 , 22,23 or PEDOT:PSS, 24,25 with the desired work function are often used as the interlayer to transport electrons or holes from the active layer to the electrode.…”
Section: ■ Introductionmentioning
confidence: 99%